2014
DOI: 10.1155/2014/369687
|View full text |Cite
|
Sign up to set email alerts
|

Is Repeat PTA of a Failing Hemodialysis Fistula Durable?

Abstract: Purpose. Our objective was to evaluate the outcome of percutaneous transluminal angioplasty (PTA) and particularly rePTA in a failing arteriovenous fistula (AV-fistula). Are multiple redilations worthwhile? Patients and Methods. All 159 stenoses of AV fistulas that were treated with PTA, with or without stenting, during 2008 and 2009, were included. Occluded fistulas that were dilated after successful thrombolysis were also included. Median age was 68 (interquartile range 61.5–78.5) years and 75% were male. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 28 publications
(18 reference statements)
2
47
2
4
Order By: Relevance
“…The current Society for Vascular Surgery guidelines recommend using both endovascular and open surgery to maintain and to restore the patency of AVFs and AVGs; however, because of the limited data available, this recommendation is based on only grade 2 evidence. 2 Bountouris et al 3 showed that 50% of AVFs and AVGs undergoing percutaneous transluminal angioplasty (PTA) will ultimately require reintervention, indicating that multiple percutaneous interventions are often performed in an attempt to prolong or to restore functional patency of arteriovenous access. Although it is common, the results of a strategy of repeated percutaneous intervention on failing arteriovenous access have not been well described.…”
mentioning
confidence: 99%
“…The current Society for Vascular Surgery guidelines recommend using both endovascular and open surgery to maintain and to restore the patency of AVFs and AVGs; however, because of the limited data available, this recommendation is based on only grade 2 evidence. 2 Bountouris et al 3 showed that 50% of AVFs and AVGs undergoing percutaneous transluminal angioplasty (PTA) will ultimately require reintervention, indicating that multiple percutaneous interventions are often performed in an attempt to prolong or to restore functional patency of arteriovenous access. Although it is common, the results of a strategy of repeated percutaneous intervention on failing arteriovenous access have not been well described.…”
mentioning
confidence: 99%
“…В некоторых исследованиях авторы делают вывод, что ýндоваскулярная ангиопластика может быть методом выбора в случае стеноза АВФ, а в случае неудачи следует прибегнуть к открытому оперативному вмешательству [33][34][35]. Другие ученые считают, что открытые операции следует выполнять у ограниченного круга больных, например, при псевдоаневризмах или при стойкой рецидивирующей дисфункции АВФ после ýндоваскулярных вмешательств [36]. Есть и сторонники мнения, что в случае рестеноза повторная ýндоваскулярная баллонная ангиопластика имеет хорошие результаты [37].…”
Section: методы лечения стенозов периферических отделов фистульной веныunclassified
“…Одни авторы считают, что срок развития стеноза после формирования АВФ -важный фактор. Ранние стенозы имеют значительно больший риск рестеноза после баллонной ангиопластики [36,[40][41][42][43]. Другие авторы, напротив, считают, что ýндоваскулярная ангиопластика наиболее ýффективна при небольших сроках функционирования АВФ или при ее замедленном созревании, в то время как у больных с длительным сроком функционирования АВФ ýтот метод не повышает выживаемость доступа [44].…”
Section: методы лечения стенозов периферических отделов фистульной веныunclassified
See 1 more Smart Citation
“…Несмотря на практически очень высокие показатели технического успеха, эндоваскулярные вмешательства несколько скомпрометированы неутешительными долгосрочными результатами -частыми и быстрыми рецидивами. Практически все авторы свидетельствуют об относительно невысокой первичной годовой проходимости АВФ -не более 50% [44,[52][53][54][55][56]. Нам не встретились исследования, анализирующие причины неэффективности различных вариантов ангиопластики.…”
Section: методы лечения стенотических поражений центральных венunclassified